Narrative review on the management of moderate-severe atopic dermatitis in pediatric age of the Italian Society of Pediatric Allergology and Immunology (SIAIP), of the Italian Society of Pediatric Dermatology (SIDerP) and of the Italian Society of Pediatrics (SIP) - Elena Galli; Anna Belloni Fortina; Giampaolo Ricci; Nunzia Maiello; Iria Neri; Ermanno Baldo; Irene Berti; Domenico Bonamonte; Lucetta Capra; Elena Carboni; Rossella Carello; Francesca Caroppo; et al. (BMC, 2022)
Abstract Currently, there are a few detailed guidelines on the overall management of children and adolescents with moderate-severe atopic dermatitis. AD ​​is a complex disease presenting with different clinical phenotypes, which require an individualized and multidisciplinary approach. Therefore, appropriate interaction between primary care pediatricians, pediatric allergists, and pediatric dermatologists is crucial to finding the best management strategy. In this manuscript, members of the Italian Society of Pediatric Allergology and Immunology (SIAIP), the Italian Society of Pediatric Dermatology (SIDerP), and the Italian Society of Pediatrics (SIP) with expertise in the management of moderate-severe atopic dermatitis have reviewed the latest scientific evidence in the field. This narrative review aims to define a pathway to appropriately managing children and adolescents with moderate-severe atopic dermatitis.